Influence of first morning urine volume, fasting blood glucose and glycosylated hemoglobin on first morning urinary albumin concentration - M.B. Gomes; M.R. Lucchetti; M.F.R. Gonçalves; H. Gazzolla; T. Dimetz; H. Matos (Brazilian Journal of Medical and Biological Research, 1997)
The aim of the present study was to evaluate the effect of first morning urinary volume (collected on three different non-consecutive days), fasting blood glucose (determined on the first and third days of urine collection), and glycosylated hemoglobin (determined on the first and third days of urine collection) on the albumin concentration in first morning urine samples collected on three different days. We found 3.6% asymptomatic bacteriuria in the urine samples; therefore, every urine sample must be tested to exclude infection. One hundred and fifty urine samples were provided by 50 IDDM patients aged 21.9 ± 7 (12-38) years with a disease duration of 6.8 ± 5.8 (0.4-31) years attending the Diabetes Clinic at the State University Hospital of Rio de Janeiro. There were no differences in albumin concentration (6.1 vs 5.8 vs 6.2 µg/ml; P = NS) or urinary volume (222.5 vs 210 vs 200 ml) between the three samples. In addition, there were no differences in fasting blood glucose (181.9 ± 93.6 vs 194.6 ± 104.7 mg%; P = NS) or glycosylated hemoglobin (HbA1)(8.4 ± 1.3 vs 8.8 ± 1.5%; P = NS) between the first and third blood samples. Six patients (group 1) had a mean urinary albumin concentration of more than 20 µg/ml for the three urine samples. This group was compared with the 44 patients (group 2) with a mean urinary albumin concentration for the three urine samples of less than 20 µg/ml. No difference was found between groups 1 and 2 in relation to fasting blood glucose (207.1 ± 71.7 vs 187.6 ± 84.6 mg/dl), HbA1 (8.1 ± 0.9 vs 8.6 ± 1.1%) or urinary volume [202 (48.3-435) vs 246 (77.3-683.3) ml]. Stepwise multiple regression analysis with albumin concentration of first morning urine samples as the dependent variable, and urinary volume, fasting blood glucose and glycosylated hemoglobin as independent variables, showed that only 12% (P = 0.01) of the albumin concentration could be accounted for by the independent effect of morning urine volume on the first day of urine collection. No urine samples showed a change in the cutoff level of 20 µg/ml of albumin concentration as the result of volume. Fasting blood glucose and glycosylated hemoglobin did not influence the urinary albumin concentration. Considerable variability in urinary albumin concentration was found in the three morning urine samples with a mean intraindividual coefficient variation of 56%. In conclusion, in the present study, urinary volume had a minimal, though not constant, effect on first morning urinary albumin concentration. Day-to-day metabolic and clinical control of IDDM patients, except probably for ketoacidosis, should not contraindicate microalbuminuria screening in first morning urine samples